Sedentary Thresholds for Accelerometry-Based Mean Amplitude Deviation and Electromyography Amplitude in 7–11 Years Old Children - Gao, Ying; Haapala, Eero A.; Vanhala, Anssi; Sääkslahti, Arja; Rantakokko, Merja; Laukkanen, Arto; Pesola, Arto J.; Rantalainen, Timo; Finni, Taija (Frontiers in Physiology, 2019)
We investigated the ability of energy expenditure, movement sensing and muscle activity to discriminate sedentary and non-sedentary activities in children. Thirty five 7−11-year-old children participated in the study. Simultaneous assessment of oxygen uptake (V̇O2), triaxial accelerometry and thigh muscle electromyography (EMG) were performed during 8 different sedentary and non-sedentary activities including lying down, sitting-, standing- and walking-related activities, which were performed in a random order. Mean values of V̇O2, accelerometry and EMG from the concurrent 2 minute epochs during each activity were computed. Resting energy expenditure (REE) was measured during 30 minute supine rest. Directly measured metabolic equivalent of tasks (METs, V̇O2 in activities/V̇O2 in REE) were calculated for each activity. Mean amplitude deviation (MAD) was computed for accelerometry. EMG was normalized for mean muscle activity during self-paced walking. The classification accuracy of METs, MAD and EMG to discriminate sedentary activities from physical activities was investigated by receiver operating characteristic curves and optimal cut-offs based on maximal sensitivity and specificity. Mean (SD) REE was 5.0±0.8 ml/kg/min. MET, MAD, and EMG values ranged from 1.0−4.9, 0.0020−0.4146g, 4.3−133.9% during lying down and walking at 6 km/h, respectively. Optimal cut-offs to discriminate sedentary activities from non-sedentary activities were 1.3 for METs (sensitivity=82%, specificity=88%), 0.0033g for MAD (sensitivity=80%, specificity=91%) and 11.9% for EMG (sensitivity=79%, specificity=92%). In conclusion, this study provides applicable thresholds to differentiate sitting and standing, and sedentary and non-sedentary activities based on METs, MAD and EMG in young children.